Clostridial Binary Toxins: Iota and C2 Family Portraits - Stiles, Bradley G.; Wigelsworth, Darran J.; Popoff, Michel R.; Barth, Holger (Frontiers in Cellular and Infection Microbiology, 2011)
There are many pathogenic Clostridium species with diverse virulence factors that include protein toxins. Some of these bacteria, such as C. botulinum, C. difficile, C. perfringens and C. spiroforme, cause enteric problems in animals as well as humans. These often fatal diseases can partly be attributed to binary protein toxins that follow a classic AB paradigm. Within a targeted cell, all clostridial binary toxins destroy filamentous actin via mono-ADP-ribosylation of globular actin by the A component. However, much less is known about B component binding to cell-surface receptors. These toxins share sequence homology amongst themselves and with those produced by another Gram-positive, spore-forming bacterium also commonly associated with soil and disease: Bacillus anthracis. This review focuses upon the iota and C2 families of clostridial binary toxins and includes: 1) basics of the bacterial source; 2) toxin biochemistry; 3) sophisticated cellular uptake machinery; and 4) host-cell responses following toxin-mediated disruption of the cytoskeleton. In summary, these protein toxins aid diverse enteric species within the genus Clostridium.